Ответ:
UWU
Объяснение:
а)
[tex]\frac{1}{4}x^2+x+1=0\\D=1^2-4(\frac{1}{4})(1)=1-1=0\\x=\frac{-b}{2a}=\frac{-1}{\frac{1}{2} }=-2[/tex]
Функция = 0 при x=-2
b) [tex]f'(x)=\frac{1}{2}x+1[/tex]
[tex]f'(x)=0\\\frac{1}{2}x+1=0\\ x=-2[/tex]
- +
-------------o------------------>x
-2
Функция возрастает при x ∈ (-2;+∞)
Функция убывает при x ∈ (-∞;-2)
в)
[tex]\frac{1}{4}x^2+x +1 > 0\\x > -2\\\frac{1}{4}x^2+x +1 < 0\\x < -2[/tex]
↓ - + ↑
y>0; x ∈ (-2;+∞)
y<0; x ∈ (-∞;-2)
г) [tex]f'(x)=\frac{1}{2}x+1[/tex]
Точка минимума
f(-2)=[tex]\frac{1}{4}(-2)^2+(-2)+1=1+1-2=0[/tex]
MIN f(x)=f(-2)=0
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
UWU
Объяснение:
а)
[tex]\frac{1}{4}x^2+x+1=0\\D=1^2-4(\frac{1}{4})(1)=1-1=0\\x=\frac{-b}{2a}=\frac{-1}{\frac{1}{2} }=-2[/tex]
Функция = 0 при x=-2
b) [tex]f'(x)=\frac{1}{2}x+1[/tex]
[tex]f'(x)=0\\\frac{1}{2}x+1=0\\ x=-2[/tex]
- +
-------------o------------------>x
-2
Функция возрастает при x ∈ (-2;+∞)
Функция убывает при x ∈ (-∞;-2)
в)
[tex]\frac{1}{4}x^2+x +1 > 0\\x > -2\\\frac{1}{4}x^2+x +1 < 0\\x < -2[/tex]
↓ - + ↑
-------------o------------------>x
-2
y>0; x ∈ (-2;+∞)
y<0; x ∈ (-∞;-2)
г) [tex]f'(x)=\frac{1}{2}x+1[/tex]
[tex]f'(x)=0\\\frac{1}{2}x+1=0\\ x=-2[/tex]
- +
-------------o------------------>x
-2
Точка минимума
f(-2)=[tex]\frac{1}{4}(-2)^2+(-2)+1=1+1-2=0[/tex]
MIN f(x)=f(-2)=0